Quantitative shunt imaging in the evaluation of therapeutic surgery in a patient with pulmonary arteriovenous malformation - DEDE, FUAT; TUROĞLU, HALİL TURGUT; İNANIR, SABAHAT; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ (ELSEVIER SCIENCE INC, 2008)
A case of pulmonary arteriovenous malformation (PAVM) in a 32-year-old woman who underwent successful left upper lobectomy is presented. A whole-body technetium-99m-labeled macro-aggregated albumin scan was used to demonstrate intrapulmonary right-to-left shunt, and shunt fraction was calculated as 39%. The patient underwent a follow-up scan after the operation

shunt fraction was calculated to be within normal limits (5%). The whole-body technetium-99m-labeled macro-aggregated albumin scan seems to be a simple and noninvasive test in the demonstration and quantitation of the degree of the right-to-left shunt in pulmonary arteriovenous malformation. The whole-body technetium-99m-labeled macro-aggregated albumin scan may also be useful for evaluation of the hemodynamic changes after surgical treatment and follow-up of the patients with pulmonary arteriovenous malformation.